Um estudo sobre argumentação e prova envolvendo o teorema de Pitágoras - Ferreira Filho, José Leôncio (2007)
The National Curriculum Parameters (Brazil, 1998), acknowledge and recommend that the Mathematics syllabus should necessarily cover activities and experiences which enable learners to develop and effectively communicate with valid mathematical argumentation. However, there is consensus among Mathematics Education researchers, in several countries, as to the inherent difficulties of teaching and learning proof. This research is inserted in the AprovaME project, in the Mathematics Education area at PUC-SP, which has as one of its goals to foster debate over the teaching and learning of proof in Mathematics. The objective of the present study was to investigate the involvement of first-year students at high school in processes of conjecture and proof construction, aiming to answer the following research question: what difficulties do students present when faced with argumentation and proof situations involving the Pythagorean Theorem? In order to answer the research question, we adopted some elements from the didactic engineering as the research methodology. A teaching sequence was then elaborated with questions on argumentation and proof involving the Pythagorean Theorem and applied to students from a private school in a countryside city in the State of Sao Paulo. The work by Robert (1998) and Duval (2002) contributed to the conception of activities, and the ones by Balacheff (1988), to the analysis of the types of proof from the students. The production from the students, at the end of the activities, show that the teaching sequence conceived to produce argumentation and proof advantaged the passing of a step where validations are predominantly empirical into another step, in which validation takes on a deductive character. Other studies approaching different mathematics topics and which treat teaching and learning of proof have become more and more needed for understanding the complexity surrounding this process